Let φ = 2 1 + 5 . Given that φ 1 4 = a + b φ , where a and b are positive integers, find the value of a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I was so sure of my addition skills that i added 233 and 377 to 600... Three times in a row.
omg that is so cool :D i didn't know that propertie
Very nice.
That is the way that I solved it too.
but 'a' can be = 0 right? so
[; \frac{\phi^{14}}{\phi}=b=521 ;] and [; \phi * 521 + 0= \phi^{14} ;]
Log in to reply
No a can't be 0. Why do you think it is?
It should be enclosed in \ [ and \ ], not [; and ;].
lol it's fibonacci numbers!
golden ratio (1+sqrt5)/2 is a root of equation x^2 = x + 1 so you dont have to calculate them all to experiment. and u can just add them all till x^14 cuz 14 isnt a very big number and adding numbers isnt difficult. so yeah... i did it the lazy way... i didnt wanna force my brain to work lol
Consider the fact that ϕ is the solution to the quadratic ϕ 2 − ϕ − 1 = 0 , then it better be the case that ϕ 2 = 1 + ϕ . By elimination, it's easy to see that the extension Z [ ϕ ] (all numbers of the form a + b ϕ ) is closed under addition and multiplication! ( a + b ϕ ) ( c + d ϕ ) = a c + ( b c + a d ) ϕ + b d ϕ 2 = ( a c + b d ) + ( b c + a d + b d ) ϕ therefore arithmetic on Z [ ϕ ] can be alternatively characterized on the field Φ = ( Z 2 , ⊕ , ⊗ ) whereby ⊕ is just addition over integer componentwise and ( a , b ) ⊗ ( c , d ) = ( a c + b d , a d + b c + b d ) Now, recall that ( a + b ϕ ) ϕ = a ϕ + b ϕ 2 = b + ( a + b ) ϕ , so ( a , b ) ( 0 , 1 ) = ( b , a + b ) : ϕ ϕ 2 ϕ 3 ϕ 4 ϕ 5 ⋮ = ( 0 , 1 ) = ( 0 , 1 ) ( 0 , 1 ) = ( 1 , 1 ) = ( 1 , 1 ) ( 0 , 1 ) = ( 1 , 2 ) = ( 2 , 3 ) = ( 3 , 5 ) let the second component of ϕ k be f k and the first component f k − 1 , then ( f k , f k + 1 ) = ( f k − 1 , f k ) ( 0 , 1 ) = ( f k , f k − 1 + f k ) , therefore, this is entirely characterized by the recurrence f 0 = 0 , f 1 = 1 , f k + 1 = f k + f k − 1 , which turns out to be the fibonacci numbers! Anyways, this gives ϕ k = ( f k − 1 , f k ) so the value of a + b for ϕ 1 4 must be f 1 3 + f 1 4 = f 1 5 , which in this case is 6 1 0
If you don't have a calculator, you can also compute f 1 5 by looking at ϕ 1 6 , which you can get by computing the sequence ϕ , ϕ 2 , ϕ 4 , ϕ 8 , ϕ 1 6 which should take just 5 computations to complete, if you start at ϕ 2 and you only compute the first element of ϕ 1 6 : ( 1 , 1 ) → ( 2 , 3 ) → ( 1 3 , 2 1 ) → ( 1 3 2 + 2 1 2 , ⋅ ) .
It is known that ϕ n = F ( n ) × ϕ + F ( n − 1 ) , where F ( n ) is the Fibonacci's n-th number.
By the Fibonacci Sequence recursion definition, F ( n − 1 ) + F ( n ) = F ( n + 1 ) . This means a + b will be the 15-th Fibonacci number, which happens to be 6 1 0 .
φ satisfy the quadratic equation φ 2 − φ − 1 = 0 . So we have φ 3 = φ 2 + φ = 2 φ + 1 And φ 4 = φ 2 + 2 φ + 1 = 3 φ + 2 . So we can calculate that φ 7 = 6 φ 2 + 7 φ + 2 = 1 3 φ + 8 And we have the result φ 1 4 = 1 6 9 φ 2 + 2 0 8 φ + 6 4 = 3 7 7 φ + 2 3 3 With a = 2 3 3 and b = 3 7 7 , we have a + b = 6 1 0
We prove by induction φ n = f n φ + f n − 1 We have φ 2 = φ + 1 Assume that the statement holds for n. φ n + 1 = φ ( f n φ + f n − 1 ) = f n ( φ + 1 ) + f n − 1 φ = f n + 1 φ + f n Then the statement also holds for n+1. So a + b = f 1 4 + f 1 3 = f 1 5 = 6 1 0
Powers of the Golden Ratio satisfy the same recurrence relation as the Fibonacci numbers, namely a n = a n − 1 + a n − 2 . From this, we see that that ϕ n = F n ∗ ϕ + F n − 1 , where F n denotes the n th Fibonacci number. Therefore, ϕ 1 4 is equivalent to F 1 4 + F 1 3 = F 1 5 = 6 1 0
First you must notice that given the formula ϕ n = ϕ n − 1 + ϕ n − 2 it yields that for n ≥ 2 , ϕ n = F n − 2 ϕ 2 + F n − 3 ϕ Where F i is the i-th Fibonacci number. Then it is easy to see that ϕ 1 4 = 3 6 7 ϕ + 2 3 3 . Therefore a + b = 2 3 3 + 3 6 7 = 6 1 0 .
Given x as a golden ratio, we have the equation x^2 = x + 1 Therefore, x^2 - x = 1 Therefore, we can prove that x^n = x^(n-1) + x(n-2) Because x^n - x^(n-1) = x^(n-2) [x^2 - x] = x^(n-2) So the a and b ratio will follow the Fibonanci series a(1) = a(2) = 1; a(n) = a(n-1) + a(n-2) b(1) =0; b(2) = 1; b(n) = b(n-1) + b(n-2)
Problem Loading...
Note Loading...
Set Loading...
By experimenting with the first few powers of φ we get:
φ = 0 + ( 1 ) φ
φ 2 = 1 + ( 1 ) φ
φ 3 = 1 + 2 φ
φ 4 = 2 + 3 φ
φ 5 = 3 + 5 φ
φ 6 = 5 + 8 φ
From here we see a relation to the Fibonnaci sequence. We can conjure:
φ n = F ( n − 1 ) + F ( n ) φ
Where F ( n ) is the fibonnaci sequence with F ( 0 ) = 1 , F ( 1 ) + 1 a n d F ( n + 1 ) = F ( n ) + F ( n − 1 ) for integers n .
We can prove it by induction. The iductive step would be:
φ n + 1 = φ φ n
= φ ( F ( n − 1 ) + F ( n ) φ )
= F ( n − 1 ) φ + F ( n ) φ 2
= F ( n − 1 ) φ + F ( n ) ( 1 + φ )
= F ( n ) + ( F ( n − 1 ) + F ( n ) ) φ
= F ( n ) + F ( n + 1 ) φ
Hence φ 1 4 = F ( 1 3 ) + F ( 1 4 ) φ . So we need F ( 1 3 ) + F ( 1 4 ) = F ( 1 5 ) = 6 1 0